Relasi Agama dan Sains menurut Ian G Barbour dalam Moderasi Beragama di Indonesia - Wahyu; Khudori Soleh, Achmad; Wardah (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
The context of religious diversity in society is an increasingly relevant and important issue in this era of globalization. The theme of religious moderation is very important because the challenges of religious diversity in society are increasingly complex. This research aims to provide an understanding regarding religious moderation as a basis for society in dealing with differences in beliefs and building harmony amidst religious plurality. This research method uses a literature review and analysis approach to achieve the objectives of this paper. Through these two sources, the author looked for articles discussing religious moderation and then compared them with this article. In the critical analysis process, the author found differences in approach, focus, methodology, or findings discussed in previous articles and this article. The results of this research explain that, (1) religious moderation in Indonesia is unique, because the diversity of religions in Indonesia reflects the diversity of religious beliefs, values ​​and practices. (2) Conflict or tension between religious views and scientific discoveries can disrupt social peace and scientific developments in society. (3) Ian G. Barbour's approach to dialogue and harmony is relevant in the unique Indonesian context. The conclusion from this research is that the relationship between religious views and science can be resolved in a harmonious way and build a relationship that respects each other. Ian G. Barbour's perspective, the relationship between religion and science can be explained through four approaches: conflict, independence, dialogue and integration. Religious moderation in Indonesia is an effort to create harmony between religious communities by prioritizing tolerance, dialogue and respect for differences in beliefs.